ROLE OF MEDICAL TREATMENT IN ENDOMETRIOSIS ASSOCIATED INFERTILITY - Pacheco Romero, José (2015)
It is not yet known as endometriosis occurs and why it evolves. In the etiology it is considered retrograde menstrual flow, possible endocrine changes, immune disorders and genetic factors undoubtedly yet to specify.